2003
DOI: 10.1002/ijc.11660
|View full text |Cite
|
Sign up to set email alerts
|

Antisense abrogation of DENN expression induces apoptosis of leukemia cells in vitro, causes tumor regression in vivo and alters the transcription of genes involved in apoptosis and the cell cycle

Abstract: We previously reported that messenger RNA expression of DENN (differentially expressed in normal and neoplastic cells) is considerably higher in cancer cell lines than in normal cells. In our present study, we established that certain cancer cell lines express conspicuously higher levels of the 2 DENN isoforms in contrast to the 2 pro-apoptotic IG20 isoforms. Antisense DENN oligodeoxynucleotide treatment of K36 cells in vitro induced extensive apoptosis, while antisense DENN silencing of K36 tumor-bearing mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…These observations indicated that IG20-SVs could differentially regulate cell proliferation and death. Recent studies (Lim and Chow, 2002;Lim et al, 2004) in which all four endogenous IG20-SVs were knocked down using oligodeoxynucleotides (ODNs) revealed increased susceptibility of cancer cells to apoptosis; an intriguing finding given our previous Selective knockdown of IG20-SVs in cancer cell survival N Mulherkar et al observations. Therefore, we set out to determine the specific IG20-SV responsible for cancer cell survival.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…These observations indicated that IG20-SVs could differentially regulate cell proliferation and death. Recent studies (Lim and Chow, 2002;Lim et al, 2004) in which all four endogenous IG20-SVs were knocked down using oligodeoxynucleotides (ODNs) revealed increased susceptibility of cancer cells to apoptosis; an intriguing finding given our previous Selective knockdown of IG20-SVs in cancer cell survival N Mulherkar et al observations. Therefore, we set out to determine the specific IG20-SV responsible for cancer cell survival.…”
Section: Discussionmentioning
confidence: 76%
“…Knockdown of all endogenous IG20-SVs, using antisense oligonucleotides, resulted in spontaneous apoptosis of cancer cells in vitro and in vivo (Lim and Chow, 2002;Lim et al, 2004). Therefore, contrasting effects of IG20-SVs, noted earlier, can only be clarified by knocking down individual IG20-SVs and determining the consequent effects.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Total RNA was isolated from frozen lung tissues using the RNeasy Plus Mini kit (Qiagen, Hilden, Germany), and reverse-transcribed into cDNA with the MMLV Reverse Transcription system (Promega, Madison, WI) using random primers (32). Aliquots of cDNA (1 ml each) were amplified by PCR using SP-C, T1-a, HGF, and b-actin primers ( Table 1).…”
Section: Semi-quantitative Rt-pcrmentioning
confidence: 99%
“…At 0, 1, 4, and 7 h postinfection, both infected and uninfected cells were fixed with 2.5% glutaraldehyde in 0.1 M phosphate buffer (pH 7.4) at room temperature for 1 h. The fixed samples were then postfixed with 2% osmium tetroxide at room temperature for 1 h, dehydrated in a graded alcohol series, and embedded in Epon 812. Ultrathin sections (20 nm thick) were cut with a microtome, stained with uranyl acetate and lead citrate for 20 and 10 min, respectively, and observed using a Philips model 208S electron microscope (26).…”
Section: Methodsmentioning
confidence: 99%